Validation of the Malay version of Mini-IPIP and TIPI among substance use disorder patient attending methadone clinics in Perak and Kelantan, Malaysia - Weng, Leong Foo (2018)
Background There has been an increasing interest in personality study over the years. This has led to the necessity for personality measures with good psychometric properties. However, good personality measures are usually too cumbersome to apply in real practical settings due to their length. This study aims to validate two commonly used short personality measures of the Big Five model in various contexts including substance abuse, i.e. Mini-IPIP and TIPI, but has never been validated and used in Malaysia. Methods Forward and back translations, content validity, and face validity were carried out on Mini-IPIP and TIPI in which both were then used in the pilot study. Finalised version of the questionnaires were used in the validation study involving 239 participants collected through convenience sampling from six methadone clinics in Perak and Kelantan. The construct validity of the questionnaires was assessed using confirmatory and exploratory factor analyses. Results Results showed a good model fit for Mini-IPIP when item-parcelling and adding-in correlated uniqueness items were applied (CFI/TLI = .949/.831, RMSEA = .094, SRMR = .044). As for the TIPI, five factor structure was extracted and cross-loadings were observed for the items between the factors. Conclusion Our study supported the five factor solution for Mini-IPIP. However, there were poor factor loading in the items factor for TIPI. Further revision is needed for the current Malay version of TIPI. Both instruments can be used in time-limited settings and when researchers are willing to compromise the lower validity and reliability aspects of these shorter personality measures.